Effectiveness of a rehabilitation program involving functional proprioceptive stimulation for postural control and motor recovery among stroke patients: a double-blinded, randomized, controlled trial - Agnieszka Wiśniowska-Szurlej; Justyna Leszczak; Justyna Brożonowicz; Gabriela Ciąpała; Héctor Hernández-Lázaro; Agnieszka Sozańska (Journal of NeuroEngineering and Rehabilitation)
Abstract Background Early and intensive rehabilitation is particularly important for increasing neuroplasticity in patients after stroke. The aim of this study was to evaluate the effects of a 4-week rehabilitation program involving functional proprioceptive stimulation (FPS) on postural control and functional recovery in patients with stroke. Methods This double-blinded, randomized controlled trial (RCT) was conducted at a tertiary care rehabilitation centre. Fifty patients with first stroke were recruited and randomly separated into a FPS Group (n = 25) or Sham Group (n = 25). Both groups underwent 3.5 h of rehabilitation, including physiotherapy, occupational therapy, verticalization and focal vibration on specific myotendinous junctions of the leg, for 5 days a week over 4 successive weeks. For the sham group, the focal vibrations had an amplitude of 0.1 mm with a fixed frequency of 40 Hz. For the FPS group, the stimulation consisted of focal vibrations of an amplitude of 2 mm with frequencies constantly changing between 40 and 85 Hz. Postural control evaluation was performed with the Berg Balance Scale (BBS), Functional Reach Test (FRT) and via the Alfa AC International East stabilometric platform; motor recovery was examined via the Barthel Index (BI) and ICF Rehabilitation Set. All assessments were performed at baseline and after intervention. Results Following the intervention, the FPS Group demonstrated clinically significant improvements in postural control and functional status (BBS p = 0.041 and BI p = 0.037). A statistically significant improvement was also obtained in the Sham Group in the FTR test. Patients in the FPS Group experienced significantly greater improvement than those in the Sham Group on D420 (transferring oneself) and D640 (performing housework activities). Conclusions Our study showed that conventional rehabilitation and rehabilitation combined with functional proprioceptive stimulation both improve balance and functional efficiency in people after. Trial registration The study was registered at ClinicalTrials.gov (NCT05550987).